Effect of Time Budget Pressure and Locus of Control of Auditor Dysfunctional Behaviors (Survey on Legislative Auditor BPKP Gorontalo Province) - Sari, Ratna; -, enriwaru; Mokodongan, Agung Pribadi (Journal of Education and Vocational Research, 2016)
This research aims to examine the influence of time budget pressure and locus of control to dysfunctional audit behavior (survey on Representative BPKP Government in Gorontalo Province). This research uses primary data collected directly from respondents. Population in this research is the auditors who work at BPKP’s of Gorontalo Province. And sample in this research used 34 auditors as respondents by using census method. Data collected was analyzed using test data quality, classic assumption test and multiple linear regression analysis. The results showed: partially, time budget pressure is positive and significant toward dysfunctional audit behavior while the locus of control is positive but no significant to dysfunctional audit behavior. Simultaneously, time budget pressure and locus of control are significant to dysfunctional audit behavior.